Efek Iritasi Sabun Mandi Batang Mengandung Susu Produk Usaha Kecil Menengah di Kota Cimahi - Vikasari, Suci Nar; Hermanto, Faizal; Simatupang, Elivas; Sutjiatmo, Afifah Bambang; Sutarna, Titta Hartyana; Puspadewi, Ririn; Rachmawan, Lucky; Haq, Fahmy Ahsanul (Jurnal Kefarmasian Indonesia, 2020)
One of the ways to increase profit in small and medium business (UKM) in Cimahi is by diversifying its products, through manufacturing of bar soap derived from cow's milk from UKM. The requirement of bath soap is proper acidity (pH) level, otherwise it will make the skin dry, itchy or even increase irritation. Therefore, this in vivo non-clinical irritation evaluation is conducted to evaluate the effects of bar soap produced by UKM in Cimahi according to the guidelines in rat test animals. The animals is divided into five groups and exposed to soap for four hours. Five soap samples is obtained from UKM in Cipageran area, Cimahi. Observations is made at the hours of 1, 4, 24, 48, and 72 hours after exposure and is continued for 14 days. The measured parameters is erythema and edema, and the primary irritation index. The results showed that bar soap containing cow milk produced by UKM in Cimahi did not cause erythema and edema. Primary irritation index of all bath soap samples was 0.0 . It can be concluded that soap bars containing cow's milk produced by Cimahi City UKM including into the category of very mild irritation (negligigle).